2021
DOI: 10.1016/j.esmoop.2021.100086
|View full text |Cite
|
Sign up to set email alerts
|

Blood-based genomics of triple-negative breast cancer progression in patients treated with neoadjuvant chemotherapy

Abstract: Background: As neoadjuvant chemotherapy (NAC) is increasingly used in triple-negative breast cancer (TNBC), we investigated the value of circulating tumor DNA (ctDNA) for patient monitoring prior, during, and after NAC, and circulating tumor cells (CTCs) for disease characterization at clinical progression. Materials and methods: Forty-two TNBC patients undergoing NAC were prospectively enrolled. Primary tumor mutations identified by targeted-gene sequencing were validated and tracked in 168 plasma samples lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 28 publications
2
31
0
Order By: Relevance
“…Various studies in neoadjuvantly-treated breast cancer patients found that ctDNA levels and mutations were significantly different between breast cancer subtypes ( 9 , 11 , 40 , 41 ). Expression levels of the proliferation-associated nuclear protein, Ki-67, have also been directly associated with ctDNA characteristics in breast and lung cancers ( 42 44 ). Studies assessing ctDNA in non-small cell lung cancer (NSCLC) patients found that ctDNA concentration was correlated with tumor stage, histology, and degree of cytological atypia ( 45 47 ).…”
Section: Biological Factors That Most Affect Circulating Tumor Dna Ab...mentioning
confidence: 99%
“…Various studies in neoadjuvantly-treated breast cancer patients found that ctDNA levels and mutations were significantly different between breast cancer subtypes ( 9 , 11 , 40 , 41 ). Expression levels of the proliferation-associated nuclear protein, Ki-67, have also been directly associated with ctDNA characteristics in breast and lung cancers ( 42 44 ). Studies assessing ctDNA in non-small cell lung cancer (NSCLC) patients found that ctDNA concentration was correlated with tumor stage, histology, and degree of cytological atypia ( 45 47 ).…”
Section: Biological Factors That Most Affect Circulating Tumor Dna Ab...mentioning
confidence: 99%
“…Details on ctDNA analysis and predictive/prognostic significance during neoadjuvant therapy have been previously reported (Ortolan et al 2021 ). All clinical and research staff were blinded as to ctDNA and follow-up outcomes, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Breast cancer cells shed DNA into the blood, and interest in using ctDNA as a sensor to anticipate relapse in advance of clinical manifestation has grown in parallel with the improvement of techniques for its detection (Merker et al 2018 ; Page et al 2021 ). The present work builds on our experience with prospective longitudinal ctDNA monitoring before, during and after neoadjuvant therapy for triple negative breast cancer (Ortolan et al 2021 ). Clinicians were blinded to the results of ctDNA assessment and continued to monitor patients according to their clinical practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients in the control group were given laparoscopic radical surgery with the following specific steps. The modified bladder lithotomy position was taken and a cushion was put under the buttocks of the patient, an incision was made at 4 cm away from the upper edge of the nabhi chakra, the casing needle was inserted to establish the pneumoperitoneum, the intraabdominal pressure was maintained between 12 and 15 mmHg, the laparoscopy was inserted to observe the abdominal cavity and the pelvic cavity, and the hysterectomy was performed according to the image displayed by the laparoscopy; after surgery, the wound was rinsed, sutured, disinfected, and bound up [ 16 18 ].…”
Section: Methodsmentioning
confidence: 99%